Jacques Derrida n’est pas mort. Réponses de Safaa Fathy données en forme d’essai: Жак Дерида не е мртов. Одговори на Сафа Фати во облик на есеј - Fathy, Safaa; Hadzi-Lega, Joana (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Safaa Fathy | Сафа Фати Title (French): Jacques Derrida n’est pas mort. Réponses de Safaa Fathy données en forme d’essai Title (Macedonian): Жак Дерида не е мртов. Одговори на Сафа Фати во облик на есеј Translated by (French to Macedonian): Joana Hadzi-Lega | Јоана Хаџи-Лега Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 21-26 Page Count: 6 Citation (French): Safaa Fathy, “Jacques Derrida n’est pas mort. Réponses de Safaa Fathy données en forme d’essai,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 21-26. Citation (Macedonian): Сафа Фати, „Жак Дерида не е мртов. Одговори на Сафа Фати во облик на есеј“, превод од француски Јоана Хаџи-Лега, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 21-26.